Use of Family Care Indicators and Their Relationship with Child Development in Bangladesh (Journal of Health, Population and Nutrition, 2010)
Poor stimulation in the home is one of the main factors affecting the development of children living in poverty. The family care indicators (FCIs) were developed to measure home stimulation in large populations and were derived from the Home Observations for Measurement of the Environment (HOME). The FCIs were piloted with 801 rural Bangladeshi mothers of children aged 18 months. Five subscales were created: 'play activities' (PA), 'varieties of play materials' (VP), 'sources of play materials', 'household books', and 'magazines and newspapers' (MN). All subscales had acceptable short-term reliability. Mental and motor development of the children was assessed on the Bayley Scales of Infant Development and their language expression and comprehension by mothers' report. After controlling for socioeconomic variables, VP and PA independently predicted four and three of the developmental outcomes respectively, and MN predicted both the Bayley scores. The FCI is promising as a survey-based indicator of the quality of children's home environment. Key words: Care-giving behaviours; Child development; Cognitive development; Family care indicators; Home environment; Bangladesh DOI: 10.3329/jhpn.v28i1.4520 J Health Popul Nutr 2010 Feb; 28(1): 23-33